HANDMADE HUSTLE: ETSY, WHITENESS, AND GENDERED PRECARITY - Johnson, Jacqueline Elizabeth (AoIR Selected Papers of Internet Research, 2021)
Since the e-commerce site’s launch in 2005, Etsy has branded itself as a platform for individuals to buy and sell unique, handmade, and vintage items. This project is interested in questions about gender, race, labor, and platforms and seeks to examine how Etsy articulates new formations of raced and gendered labor directly tied to The Great Recession. While scholars have analyzed Etsy’s relationship to historic craft movements (Krugh 2014; Luckman 2013) and to fan handicrafting (Cherry 2016), there is still relatively little published research on the platform. Situating Etsy within the literature on postfeminism and media culture (Gill 2007; McRobbie 2004), gender and passionate work (Duffy 2016; Duffy 2017; McRobbie 2018), and race and digital hustle economies (McMillan Cottom 2020), I analyze products sold on Etsy that rhetorically engage gendered labor dynamics and precarity through the language of hustling or entrepreneurship in ways that center white femininities. Utilizing a cultural studies framing and critical discourse and textual analysis, I identify three main threads: 1) White women on the platform have co-opted Black vernacular to address how economic insecurity has pushed them into gig labor 2) These products romanticize precarity by positioning feminized grit and individualized solutions to macro economic hurdles as female empowerment 3) The products discursively frame entrepreneurship as aspirational, liberatory, and, most centrally, compatible with white, domestic femininities. While hustling, and its new, white appearance, is celebrated on Etsy, we must be mindful of how hustling is always raced, gendered, and precarious.